EKSPLORASI DAN UJI DAYA HAMBAT BAKTERI ENDOFIT DARI TANAMAN BENALU SAWO (Helixanthera sp.), BENALU COKLAT (Scurulla sp.) DAN BENALU KOPI (Helixanthera sp.) TERHADAP Escherichia coli - Febri Walpajri; Rodesia Mustika Roza; Fitmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Endophytic bacteria are microscopic microorganisms that live in the tissues of plants such as leaves, roots, fruits and stems. The parasite plants on sapodilla (Helixanthera sp.), cocoa (Scurulla sp.) and coffee (Helixanthera sp.) are medicinal plants. Theseplants have endophytic bacteria that have antibacterial compounds as antibiotics that inhibit the growth of Escherichia coli. The purpose of this study was to get endophytic bacteria isolates from parasite plants on sapodilla, cocoa and coffee, and determine the antibacterial activity against E. coli. Sampling was conducted in Kampar regency and Pekanbaru city. The parasite plants were collected from the field and their endophytic bacteria were selected using surface sterilization method and purified before their activity against E. coli being tested. The selected bacteria were then characterized. The results obtained 34 endophytic bacterial isolates that had activity against E. coli. Endophytic bacteria isolates which had the highest activity against E. coli isolates were Bbs4 from sapodilla parasites with 12,1 mm inhibition zone diameter.